Islamic Acculturation and Local Tradition in the Gumbregan Ritual: The Dynamics of Islamic Expression in the Gunungkidul Community - Sandya Sahisnu Prabaswara; Fachri Syauqii (Warisan: Journal of History and Cultural Heritage, 2025)
This study investigates the Gumbregan tradition in Gunungkidul as a dynamic site of cultural acculturation between ancestral agrarian ritual practices and Islamic normative frameworks. It addresses the question of how Islamic teachings are integrated into pre-Islamic symbolic structures without erasing local cultural identity. Employing a qualitative design that combines library research with in-depth field interviews involving religious leaders, cultural custodians, and community members, the study applies an anthropological approach grounded in acculturation theory. The findings reveal that Gumbregan operates not merely as a livestock-blessing ceremony but as a negotiated religious expression in which Islamic elements—such as supplication, ritual purification, and communal kendhuren—recontextualize inherited symbols while preserving their socio-cultural significance. This adaptive integration generates a localized model of Islamic practice that reinforces gratitude to Allah, strengthens communal solidarity, and sustains agrarian cohesion. The study argues that Islamic norms are internalized through symbolic reinterpretation rather than cultural replacement, demonstrating the community’s conscious strategy to maintain cultural continuity while affirming religious identity within an evolving Islamic framework.